Attitudes, beliefs, and changing trends of cannabidiol (CBD) oil use among caregivers of individuals with Alzheimer's disease - Magdalena Leszko; Senthil Meenrajan (Elsevier, 2021)
Objectives: With the increasing popularity of CBD-based products, especially CBD oil, it is increasingly important to understand what motivates caregivers of individuals with Alzheimer's disease (AD) to use CBD oil as part of treatment. The purpose of this study was to identify the attitudes and beliefs of caregivers of individuals with AD toward CBD oil in Poland, to identify factors that might be associated with the decision to use CBD oil among caregivers, and to explore whether such a decision was discussed with a healthcare professional. Method: A cross-sectional online survey was conducted in Poland. Participation in the study was entirely voluntary and completely anonymous. Caregivers (n = 73) were asked about their practices and attitudes regarding CBD oil. Results: The most common source of knowledge about CBD oil was an online support group for caregivers. The vast majority of caregivers found CBD to be effective in managing behavioral symptoms of AD and believed that healthcare professionals should offer CBD oil as a part of treatment. However, only 63 % (n = 46) reported consulting with their physician about using CBD oil. The study also demonstrated that some caregivers thought that CBD oil use was illegal in Poland and that their care-recipient may develop a dependence and withdrawal symptoms if they stopped using it. Conclusions: The results of the study highlight the positive and negative perceptions among caregivers of people with AD. The study also emphasizes the importance of enhancing communication between caregivers and healthcare professionals to discuss the use of CBD oil in the treatment of individuals with AD.